1969
DOI: 10.1080/00288233.1969.10427092
|View full text |Cite
|
Sign up to set email alerts
|

Bitter pit in Cox's Orange apples

Abstract: Calcium nitrate and calcium chloride tree sprays at different concentrations are compared. Calcium chloride, with about twice the calcium content of the nitrate, gave as good-control of bitter pit at half the concentration of the nitrate, which relates the effectiveness of these materials to their calcium content. Colour development on apples was better with calcium chloride than with the nitrate. The slow movement of calcium through apple flesh is demonstrated. When inadequate calcium sprays are used, -bitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Although field spraying with calcium salts throughout the growing season has been generally adopted, satisfactory control is often not obtained and pit remains a major problem in the storage and marketing of susceptible varieties. The lack of complete control could be due partly to the difficulty of ensuring complete coverage of the fruit by the sprays, as the only fruit to receive any benefit are those that are actually contacted by the sprays (Schumacher et al 1966;Chittenden et al 1969) . Wilkinson & Fidler (1973) have recently reviewed the literature on the development and control of pit and report that although the primary cause of pit is attributable to a calcium deficiency in the fruit, the disorder may be aggravated by the presence of high concentrations of potassium and magnesium.…”
Section: Introductionmentioning
confidence: 99%
“…Although field spraying with calcium salts throughout the growing season has been generally adopted, satisfactory control is often not obtained and pit remains a major problem in the storage and marketing of susceptible varieties. The lack of complete control could be due partly to the difficulty of ensuring complete coverage of the fruit by the sprays, as the only fruit to receive any benefit are those that are actually contacted by the sprays (Schumacher et al 1966;Chittenden et al 1969) . Wilkinson & Fidler (1973) have recently reviewed the literature on the development and control of pit and report that although the primary cause of pit is attributable to a calcium deficiency in the fruit, the disorder may be aggravated by the presence of high concentrations of potassium and magnesium.…”
Section: Introductionmentioning
confidence: 99%
“…Although this may be regarded as of little significance on varieties such as 'Cox's Orange', it could be of commercial importance on highly coloured varieties. Calcium chloride had no adverse effect on colour, and as the chloride is as effective as the nitrate on an equal calcium basis for control of bitter pit (Chittenden et al 1969), there is justification for its use on coloured varieties. Some workers have disputed this effect of calcium nitrate on apple colour (Atkinson 1971), but over the past 8 years it has been recorded to some degree in our trials with 'Cox's Orange' and markedly in one trial on 'Red Delicious '.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that the apple fruits themselves must be completely sprayed with calcium for bitter pit control (Chittenden et al 1969) and, later in this paper, that unsprayed apples gain no benefit from calcium sprayed on the foliage. This indicates that any increase in fruit Ca can accrue only from that applied to the apple surface.…”
Section: Calcium Levels In Fruit Sampledmentioning
confidence: 98%
See 2 more Smart Citations